PEMBINAAN KADER DA’I DI PONDOK PESANTREN NURUL ISLAM - Khairunnisa' Khairunnisa'; Yohandi Yohandi; Mokhammad Baharun (Fakultas Dakwah Universitas Ibrahimy, 2020)
Coaching is a continuous effort to train, educate and develop a personality base that is owned by a person in achieving an perfection with the talents that are owned by each character and personality. conducted by the boarding board administrators who function as implementing policies, especially those relating to the field of propaganda to give birth to preachers and preachers who are professionals to spread Islamic teachings. The findings from the field show that the training of cadre cadre by Nurul Islam Islamic Boarding School is still not effective. Only recruiting cadres from Nurul Islam preachers who are already members but not yet coordinated, young Nurul Islam cadres from students such as IKSANI AND KANSAS During the 2015-2020 period there was no evaluation. In the cadre coaching process there are several obstacles including restructuring the organization that has not been regulated and the cadre system does exist but is not yet effective